(untitled) (Anclajes, 2023)
This article analyzes Silvina Pachelo’s illustrated edition of Esteban Echeverría’s El matadero with the aim of exposing how the Buenos Aires painter rewrites one of the foundational works of Argentine literature through a visual code. Taking as a starting point the concept of the illustrator as critic, proposed by Lorraine Janzen, I argue that the illustrations offer a space of visibility to the female subjects who, marginalized in Echeverría’s text, point to the endemic state of violence against women in Latin America and that, especially in the last ten years, has been exposed in literature through different aesthetic formalizations. The result is a tense but productive dialogue between word and image that updates, once again, a work that seems to be inexhaustible in its interpretation.